1999
DOI: 10.1177/0272431699019003003
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Bullying Behavior in Middle School Students

Abstract: In this study, bullying was examined as a continuum of mild-to-extreme behaviors, and the potential correlates of bullying others were delineated. To improve identification and targeting of those youth at risk for bullying, demographic, behavioral, and psychosocial correlates were tested on a continuous measure of bullying behavior rated according to the number and frequency of behaviors. Among 558 middle school students surveyed in 1995, only 20% reported no bullying behavior. In multiple regression analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
267
5
24

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 379 publications
(317 citation statements)
references
References 37 publications
21
267
5
24
Order By: Relevance
“…Most researchers on bullying -focusing on students -have employed quantitative methodologies using large samples (Bosworth, Espelage, and Simon, 1999). For example, only 10% of bullying studies reported between 2000 and 2004 utilised a qualitative methodology (Powell et al, 2008), Consequently, to develop a much broader, and deeper approach surrounding the issues generated within the school context and to consider more implicitly the issues and questions raised, this empirical groundwork utilised an interpretive approach (Walsh, White, and Young, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Most researchers on bullying -focusing on students -have employed quantitative methodologies using large samples (Bosworth, Espelage, and Simon, 1999). For example, only 10% of bullying studies reported between 2000 and 2004 utilised a qualitative methodology (Powell et al, 2008), Consequently, to develop a much broader, and deeper approach surrounding the issues generated within the school context and to consider more implicitly the issues and questions raised, this empirical groundwork utilised an interpretive approach (Walsh, White, and Young, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire was presented to the entire class and each student was asked to answer each question as it was read aloud by a member of the research team. The three instruments that were included were: (1) the Stress in Children Questionnaire [22], (2) the Modified Aggression Scale [7,23], and (3) the Weinberger Adjustment Inventory (WAI) [24].…”
Section: Methodsmentioning
confidence: 99%
“…Hoover and colleagues [6] defined bullying as the physical or psychological abuse of an individual. The majority of the studies done in the United States have examined bullying as a subset of aggressive behavior that has potential to cause physical or psychological harm [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Olweus (1993Olweus ( , 1994 constatou que um em cada sete alunos das escolas norueguesas esteve envolvido em ações de bullying, quer como vítima quer como responsável por atos de violência. Estudos feitos em vários países revelam que os comportamentos de bullying são comuns (BOSWORTH; ESPELAGE; SIMON, 1999) e que pelo menos 15% dos estudantes estão envolvidos nesses comportamentos (SUDERMANN et al, 1996). Os pesquisadores observam também que quando a intimidação acontece, muitas vezes não é denunciada.…”
Section: Introductionunclassified